100 GHz waveguide band-pass filter employing UV-LIGA micromachining process. (November 2017) - Xin, Wang; Binzhen, Zhang; Junlin, Wang; Junping, Duan
Abstract: In this paper, a 100 GHz rectangular waveguide band-pass filter with two transmission zeros symmetrically located at both ends of pass-band is presented. The four-pole filter with two transmission zeros is composed of two dual-mode resonators with unequal width, two WR-10 standard waveguide interfaces, and three groups of round corner inductive irises in series. The filter is designed and analyzed based on the Synthesis and Simplification Theory of coupling matrix, simulated by using commercial full-wave simulation software HFSS, and fabricated using UV Lithography Technology with SU-8 photo-resist. The specifications of the filter are as follows: 100 GHz center frequency with 3.7% fractional bandwidth, the transmission zeros at frequency of 97.75 GHz and 102.75 GHz respectively to improve the out of band rejection, and return loss which is better than −18 dB across the whole pass-band. Results from measurement are in good agreement with simulations considering the inaccuracy of fabrication and measurement. Therefore, the availability of design, analysis, and fabrication methods mentioned in this paper is confirmed.